Analysis of Organizational Commitment as a Mediator of Job Satisfaction and Compensation on the Intention to Change Jobs of Bank Syariah Indonesia Employees in Madiun - Windy Ayu Riyanti; Bambang Supriadi; Nanny Roedjinandari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employee turnover can disrupt organizational stability and increase recruitment costs. This study focuses on the phenomenon of employee turnover, which poses a challenge for PT Bank Syariah Indonesia, Madiun Branch. The high turnover rate between 2021 and 2023 indicates an imbalance in compensation and job satisfaction. This research aims to analyze the effect of job satisfaction and compensation on the intention to switch jobs, with organizational commitment serving as a mediator. The research method employed is quantitative, utilizing a questionnaire distributed to 200 permanent employees of PT Bank Syariah Indonesia, Madiun Branch. The data were analyzed using Structural Equation Modeling (SEM) through Smart PLS software. The results indicate that job satisfaction and compensation significantly and positively affect organizational commitment, which in turn negatively impacts the intention to switch jobs. These findings underscore the importance of enhancing job satisfaction and compensation to reduce turnover rates in the workplace.